Risk factors for treatment failure in scabies: a cohort study. (1st April 2019) - Aussy, A.; Houivet, E.; Hébert, V.; Colas‐Cailleux, H.; Laaengh, N.; Richard, C.; Ouvry, M.; Boulard, C.; Léger, S.; Litrowski, N.; Benichou, J.; Joly, P.; et al.
Summary: Background: Treatment failure, which occurs in about one‐third of cases, is considered as a major factor in the increasing incidence of scabies in developed countries. Objectives: To identify predictors of treatment failure of scabies in ambulatory populations. Methods: This multicentre study compared the clinical characteristics and treatment modalities between a group of patients with scabies treated successfully and another group who were not cured 3 months after antiscabies treatment. Results: In total 210 patients with a diagnosis of scabies were included, comprising 98 patients in the treatment success group and 112 in the treatment failure group. The main risk factors for treatment failure were (i) the use of only one type of treatment, topical benzyl benzoate (BB) or oral ivermectin, vs. the combination of both treatments [odds ratio (OR) 2·15, 95% confidence interval (CI) 1·22–3·77]; (ii) the use of a single intake (vs. two) of oral ivermectin (OR 10·2. 95% CI 4·49–23·2); (iii) intake of ivermectin during a meal vs. on an empty stomach (OR 4·31, 95% CI 1·89–9·84); (iv) absence of decontamination of furnishings (OR 8·72, 95% CI 3·50–21·8), in particular sofa and cushions (OR 5·90, 95% CI 2·34–14·9), mattresses (OR 4·16, 95% CI 1·35–12·8) or car seats (OR 6·57, 95% CI 3·27–13·2) and (v) absence of written documents explaining treatment modalities (OR 5·18, 95% CI 2·57–10·4). In multivariate analysis, treatment failure was mainly associated with (i) use of a single intake (vs. two) of ivermectin (OR 6·62, 95% CI 2·71–16·2); (ii) use of BB alone vs. two intakes of ivermectin (OR 3·51, 95% CI 1·55–7·95) and (iii) absence of decontamination of furniture with acaricides (OR 5·81, 95% CI 1·96–16·7). Conclusions: Use of topical BB alone and a single intake (vs. two) of ivermectin are predictors of treatment failure.